2021
DOI: 10.1017/s0144686x21000994
|View full text |Cite
|
Sign up to set email alerts
|

Taking ‘A walk through dementia’: exploring care home practitioners’ experiences of using a virtual reality tool to support dementia awareness

Abstract: Emerging research has outlined the possibility for virtual reality (VR) experiences, which situate users into the perspective of someone living with dementia, to enhance dementia awareness. Currently, there is limited VR research that engages care home practitioners. It is imperative this population has high levels of dementia education given their requirements to provide care and support to residents, many of whom will be living with the condition. This paper reports on an exploratory qualitative study design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…These findings are in line with other research that used VR as an educational intervention to enhance demen-tia care among caregivers. [11] The emotional and visceral responses shared by participants demonstrate the power of the 360-degree video modality to facilitate the viewer's perceived sense of presence and foster reflexivity, which is in line with other findings. [19] Being able to step into another person's shoes via 360-degree videos might be a significant step or start toward breaking the wall of stigma and previously reported misunderstanding and miscommunication between care providers and PwD.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These findings are in line with other research that used VR as an educational intervention to enhance demen-tia care among caregivers. [11] The emotional and visceral responses shared by participants demonstrate the power of the 360-degree video modality to facilitate the viewer's perceived sense of presence and foster reflexivity, which is in line with other findings. [19] Being able to step into another person's shoes via 360-degree videos might be a significant step or start toward breaking the wall of stigma and previously reported misunderstanding and miscommunication between care providers and PwD.…”
Section: Discussionsupporting
confidence: 86%
“…[10] For instance, care home/facility practitioners perceived VR application on dementia as a convincing, immersive, insightful, and evocative experience that increased their awareness of and reflection on the care they have provided to PwD. [11] In Canada, feedback on the use of two VR videos (one with a man and the other, with a woman) that situated viewers in the point-of-view (POV) experiences of PwD during the transition from the community into a long-term care home was obtained from nursing students [6] and from the public. [8] Findings revealed that these 360-degree videos offered viewers an opportunity to 'live with dementia' vicariously.…”
Section: Introductionmentioning
confidence: 99%
“…Virtual spaces can be used to expand one's moral circle or moral sensitivity. For example, virtual reality (VR) and video games have been used to try to give something of the experience of being homeless, a refugee, or a dementia patient (Herrera et al, 2018;Irom, 2018;Hicks et al, 2021). The idea is that engaging in these ways will provide a deeper understanding of what these experiences are like, making one more morally sensitive to people in these situations, and expanding one's scope of moral concern to include these individuals more fully.…”
Section: Novel Virtual Experiencesmentioning
confidence: 99%
“…One study indicated that the dementia simulation program helped participants to have more empathy for people with dementia as well as enhanced understanding of dementia and risks of developing dementia, to increase their awareness of any changes in the attention and affection they give to people with dementia, and to acquire and reinforce new care strategies and change other strategies such as communication techniques [ 20 ]. Another qualitative study with health care providers also highlights that simulation of what it is to have dementia is an insightful, evocative, and convincing immersive experience that takes dementia awareness training to the next level [ 21 ]. When the general population interacts with the VR simulation of a person with dementia, results indicate that after the experience, the participants’ sense of community is increased.…”
Section: Introductionmentioning
confidence: 99%